The Effect of a Novel Training Program to Improve Trunk Stability Push Up Performance in Active Females: A Pilot Study - Kate Schwartzkopf-Phifer; Suzanne Leach; Katie Whetstone; Kevin Brown; Kyle Matsel (International Journal of Sports Physical Therapy)
# Background